Assessing the damage: analyzing the impact of the COVID-19 pandemic on accelerometer-assessed 24-hour movement behaviours in Brazilian adolescents - Lopes, Marcus V. V.; Janssen, Ian; da Costa, Bruno G. G.; de Oliveira, Bruno N.; de Mello, Gabrielli T.; Chaput, Jean-Philippe; Silva, Kelly S. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Although there is consistent evidence of unhealthy changes in the 24-h movement behaviours when comparing pre-COVID-19 periods to the early stages of the pandemic, there is limited research on long-term changes among adolescents. This study aimed to analyze both between- and within-participant differences in accelerometer-assessed 24-h movement behaviours by comparing cross-sectional and prospective data from the pre-COVID-19 period (August to December 2019) to the period following the reopening of schools for in-person classes in southern Brazil (August to December 2022). Methods This is a repeated cross-sectional design with a nested cohort. The 24-h movement behaviours (i.e., light physical activity [LIPA] and moderate-to-vigorous physical activity [MVPA], sedentary behaviour [SB], and sleep time [SPT]) were assessed by processing raw accelerometer data derived from a 24-h/7-day wrist-worn protocol. Compositional multilevel models were applied to compare the 24-h movement behaviour composition between time points for both cross-sectional and prospective data. Self-reported sociodemographic characteristics were examined as potential moderators. Results The cross-sectional and prospective samples comprised, respectively, 1276 (53% female, average age of 16.4 ± 1.1) and 249 (53% female, average age of 15.6 ± 0.8) participants. The 24-h movement behaviour composition differed between time-points in the cross-sectional (p < 0.001) and prospective samples (p < 0.001). Differences from 2019 to 2022 were explained by lower MVPA (-3.3 and -5.4 min/day in cross-sectional and prospective analysis, respectively) and a higher SB (4.7 and 34 min/day in cross-sectional and prospective analysis, respectively). No significant differences were observed for LIPA and SPT. Conclusions Differences in the 24-h movement behaviour composition comparing the cross-sectional samples, although statistically significant, were considered trivial and unlikely to have a substantial practical impact. However, considerable differences were observed in the prospective analysis. The results suggest that most of the observed changes over time were expected as a natural consequence of aging during high school, with only a small portion attributable to the residual impact of the pandemic.